Settlement Evaluation of a Concrete Face Rock-Fill Dam (CFRD) Using a Back-Analysis Method Based on Measurement Results (A Case Study of Siah-Bisheh Dam) - Mohammad Ali Abedian; Farhang Farrokhi; Reza Rasouli (Journal of Engineering and Technological Sciences, 2018)
The behavior of the Siah-Bisheh concrete face rock-fill dam in Mazandaran, Iran was investigated. Numerical analyses were performed before construction to evaluate the stability and predict the deformation of the dam. The material properties were chosen based on the results of geotechnical investigations. The amounts for deformation and settlement of the concrete surface were also calculated with the numerical model. The information from a number of geotechnical instruments was collected after construction and analyzed to measure settlement at different sections of the dam. The locations of the different deformations and their values are presented with various contours. The data were analyzed and used to revise the original numerical model of the dam. Following that, the long-term stability of the dam was evaluated, using parameters that were modified based on the measurement data. A comparison of the results from the numerical analysis and the values obtained from the dam settlement measurement showed that the initial results from the numerical model were much higher than the real values. It also showed that the number of construction layers used in the modeling of the dam had a significant effect on the obtained maximum amount of deformation.